Ad Hoc Transportation Committee List of Representitives 1972 - Samuel Heil:::Chairman, VCAG::: (1972)
A letter from Samuel Heil to the chairman of the Ventura County Association of Governments Transportation Committee outlining the appointed representatives for the Ad Hoc Transportation Committee.